Hubungan antara Kecerdasan Emosional dengan Adiksi Internet pada Kaum Muda Kristen - Utomo, Tabita Davinia; Utami, Asriningrum; Herawati (Veritas : Jurnal Teologi dan Pelayanan, 2024)
Previous research has found Internet addiction to be negatively related to emotional intelligence. This study aims to examine the relationship between these two variables in young Christians during the COVID-19 pandemic, when the Internet is frequently used for a long duration. This study used a quantitative correlational method through the Emotional Intelligence Questionnaire instrument (α = 0.890) based on Goleman's emotional intelligence theory, and the Internet Addiction Test (α = 0.893) based on Young's Internet addiction theory. There were 223 respondents aged 15-24 years (Age = 19.91; SD = 2.929) obtained through convenience sampling, with 62.8% female and 37.2% male. There was no correlation between emotional intelligence and Internet addiction (r = -0.104; Sig. = 0.120), although there was a negative correlation between managing emotions and salience (r = -0.156; Sig. = 0.020), as well as motivating oneself and neglect of duty (r = -0.234; Sig. = 0.000). These findings reinforce the assumption that the increasingly prevalent use of the Internet during the COVID-19 pandemic has changed the phenomenon of human interaction with the Internet, because the Internet is not only a means of coping strategies for negative emotions, but also supports daily activities. The results provide a new perception of the Internet for researchers, parents and coaches in helping young Christians to recognize their emotions so that they do not rely on the Internet when they want to express or suppress them.